2013
DOI: 10.1167/iovs.13-11677
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Imaging of Lamina Cribrosa Defects in Glaucoma Using Swept-Source Optical Coherence Tomography

Abstract: Citation: Takayama K, Hangai M, Kimura Y, et al. Three-dimensional imaging of lamina cribrosa defects in glaucoma using swept-source optical coherence tomography. Invest Ophthalmol Vis Sci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 37 publications
8
74
0
1
Order By: Relevance
“…However, since previous studies have shown that early glaucomatous damage is primarily found in preLC tissue, the results of our cohort with early to moderate glaucoma (MD range −7.96 to 0.63 dB) are notable (21,22). A light source with a longer wavelength, or using sweptsource OCT at 1,060 nm wavelength (25), might enable accurate measurement of microcirculation within LC tissue.…”
Section: Discussionmentioning
confidence: 64%
“…However, since previous studies have shown that early glaucomatous damage is primarily found in preLC tissue, the results of our cohort with early to moderate glaucoma (MD range −7.96 to 0.63 dB) are notable (21,22). A light source with a longer wavelength, or using sweptsource OCT at 1,060 nm wavelength (25), might enable accurate measurement of microcirculation within LC tissue.…”
Section: Discussionmentioning
confidence: 64%
“…The limited penetration issue might be resolved by using a light source with a longer center wavelength, or using swept-source OCT at 1060-nm wavelength. 41,42 One limitation of this study is that we involved only healthy subjects to test the repeatability and reproducibility of ONH perfusion measurements using OCTA with the OMAG technique. Since this was the first study testing the repeatability and reproducibility to quantify ONH perfusion using OMAG, we started with normal subjects to make sure that the flow measurements were not affected by disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The second clinical significance of this study's findings is that the FLCD-correspondent DHs were larger in area and longer in length than the noncorrespondent ones. This suggests the possibility that previous studies' reportedly higher DH prevalence in eyes with FLCD [9][10][11] was partially affected by these topographic characteristics of DH, which make DHs more easily detectable.…”
mentioning
confidence: 82%
“…6 Conversely, others have reported that DHs are associated with abnormalities of the lamina cribrosa (LC). 7,8 Disc hemorrhages occur frequently in eyes with focal LC defects (FLCDs) [9][10][11] and in fact show a considerable spatial relationship with them. [10][11][12] These findings signify that structural changes at the LC level lead to DH.…”
mentioning
confidence: 99%